El DHEAS incrementa la expresión de GluR2/3 y GLUR2 del receptor AMPA en el hipocampo de ratones C57/BL6 (2010)
ABSTRACT: Dehydroepiandrosterone sulfate (DHEA-S) is a neurosteroid that has effects such as neuromodulator of synaptic transmission and neuroprotection. The specific signaling pathways for these effects are not elucidated yet. Given that, some neurosteroids act through the activation of ionotropic glutamate receptors, therefore the effect of DHEA-S on the subunits GluR2 and GluR3 of the AMPA receptor was evaluated. Either DHEA-S or a control substance was administered to C57/BL6 mice. Subunit expression of the AMPA receptor was analyzed by Western blotting. Results show that long-term DHEA-S administration to C57/BL6 mice, increases the protein levels of the subunits GluR2 and GluR2/3 of the AMPA receptors located in the hippocampus. Due to the role of AMPA receptor, specifically GluR2 subunit in the regulation of intracellular calcium levels, cellular apoptosis, and synaptic plasticity, the study of neurosteroids as a therapeutic strategy in neurodegenerative diseases and cerebrovascular events is very relevant.